2018
DOI: 10.1093/ofid/ofx234
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Risk Factors for Chronic Chikungunya Arthralgia in Grenada, West Indies: A Cross-Sectional Cohort Study

Abstract: BackgroundChikungunya virus (CHIKV) is a re-emerging arboviral pathogen. In 2014, an explosive CHIKV outbreak occurred in Grenada, West Indies, infecting approximately 60% of the population. In approximately 50% of cases, CHIKV infection transitions to painful arthralgia that can persist for years. Elucidation of the risk factors for chronic disease is imperative to the development of effective risk management strategies and specific therapeutics.MethodsWe conducted a cross-sectional study of 240 people who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 44 publications
4
29
1
Order By: Relevance
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only rare community-based prospective studies were found to be reported in the scientific literature concerning insular Caribbean populations. [36][37][38][39][40][41] In other world regions, past exploratory research on chronicity was conducted either prospectively on hospitalized and circumscribed patient samples or retrospectively amidst the general population. 5,[12][13][14] In light of the emerging public health burden of CHIK disease for the Caribbean region and the Americas, the present study aims mainly to provide a more comprehensive description of the epidemiological characteristics and health outcomes of chronic stage CHIK cases in the general population of Martinique.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were reported on Reunion Island and during other investigations. 12,14,20,[36][37][38]43,[47][48][49][50] These trends could be explained by the fact that a higher humoral immune response during acute CHIK infection phase could be associated with evolution toward chronic stage CHIK and persistent arthlagia. 51 Indeed, women, as compared with men, are known to have a stronger humoral immune system linked to female hormones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During previous outbreaks, age over 50 and female sex were shown to be the main risk factors for chronic chikungunya disease [6,32,34,40,41,48,49]. Some studies focusing on gender have suggested that the menstrual cycle [50] and ovulation influence the production of proinflammatory cytokines by monocytes [50,51] and that estradiol plays a role in the increase of antibody production [52,53].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Infection with CHIKV causes Chikungunya fever, characterised by high fever, rash and joint pain which can be debilitating and, in some cases, persistent 3 . CHIKV infection induces a highly inflammatory state, inducing tissue damage 4 .…”
Section: Introductionmentioning
confidence: 99%